Prospek Pengembangan Usaha Budidaya Kerang Hijau (Perna viridis) Di Pulau Pasaran, Bandar Lampung - Nuning Mahmudah Noor (Jurusan Perikanan dan Kelautan, 2015)
Pasaran Island located in the Western District of Teluk Betung within 5 km from the center of Bandar Lampung. This island was known as a central anchovy in Lampung. Several attempts have been made to optimize the production of fishery there, especially anchovies, in the form of technical assistance policy to business operations. However, the potential Pasaran Island is very diverse and not limited to the anchovy, one of which is the potential for the cultivation of green mussel (Perna viridis). Mussels in Pasaran Island was cultivating in 3 years ago. This study uses a combination of aquaculture site surveys, water quality data collection, interviews and laboratory analysis of heavy metal content. With adequate environmental carrying capacity, ease of cultivation technology, the proximity of the location of the city of Bandar Lampung, food safety aspects as well as support for the various parties expected the green mussel farming can be a new icon other than Pasaran anchovy so as to improve social welfare in Pasaran Island.